Historical periodization, the end of history, and the future of transhumanism - Nyirkos, Tamas (Chrześcijaństwo-Świat-Polityka, 2025)
This article analyzes the structural analogy between eschatological speculations and the large-scale historical predictions of transhumanist philosophies. Theoretically, it relies on the argument that all substantive philosophies of history are necessarily theological, adding that such narratives are also necessarily teleological, involving an end-of-history thesis. Investigating different types of the latter, it argues that the future of transhumanism stands closest to the “agitated monotony” type as described by Alexis de Tocqueville, which also correlates with the lack of novelty both in the structure of predictions and in their content, which is most obvious in the case of social and political issues, whose handling by transhumanist authors seems hardly more than the extrapolation of present trends to the future.